The exclusion clause in government standard form of construction contracts - Abd. Hamid, Saiful Azhar (2013)
One of the functions of contract is to set out the rights, duties and liabilities of the parties to the contract. When a party fails to perform his duty, he is liable to pay damages to the innocent party. However, it is quite a normal practice for a party to expressly exclude liability in such eventuality. Such a term is generally known as exclusion clause. It essentially means that if he fails to perform the duty that he is expressly or impliedly bound to carry out under the contract, he is not liable to the other party. Exclusion in performing obligations in the event of breach of contract is an issue that often creates a dispute between the contracting parties. It is even more crucial when the contract is wholly drafted only by one party. Exclusion clauses are also found in standard forms of construction contracts. But they are worded in such a way that it is very difficult to determine with certainty that they are in fact exclusion clauses. They normally exclude the liability of the employers and thus create inequality and unfairness between the contracting parties. Therefore, the objective of this study is to identify the exclusion clauses and their effectiveness in excluding the employers’ liabilities. The scope of this study is limited to the Public Works Department standard forms of contracts. The study was carried out by analyzing the standard contract forms. The effectiveness was evaluated by examining the relevant court cases and opinions of experts. The analysis of the standard forms revealed sixteen exclusion clauses. In term of their effectiveness, by and large, the research found that, not all the exclusion clauses were effective to exclude the government’s liability to the contractor in the event of such failure of performance.